Tipificação dos produtores e dos sistemas produtivos do Vale do Forquilha em Quixeramobim-Ce - Albuquerque, Willy Farias (2006)
The present study proposes a typification of rural producers based on the methodology of agrarian system diagnosis, considering that current framing carried by the National Program to the Family Farm Strengthening (PRONAF) is done based only on producers' incomes. So, in order ro design such typification, other qualitative variables will be considered, still with the need for agroecological zoning, historical interviews and observation of accumulation trajectory. To make this work possible, the Riacho Forquilha Valley, in Quixeramobim, in central backlands of Ceara, was chosen, where is also installed the Drop of water Project (Projeto Pingo d'Água), important local productive arrangement. Four primary production systems were determined according to existing agroecological zones in the valley, but, from some systems some branches were raised, due to the accumulation trajectory. The retypification of producers and systems of local production was done and, based on collected information it was suggested another classification in order to allow the credit and the assistance to effectively arrive to other producers who would be so far out of reach